Photocatalytic degradation of naphthalene, using various nanocomposite materials mostly based on metal oxides - Vladan Nedelkovski; Milan Radovanović; Slađana Alagić (Zaštita Materijala)
Polycyclic aromatic hydrocarbons cause significant environmental and health concerns, necessitating effective remediation strategies. Specifically, biological treatments are only effective for PAH compounds with lower molecular weights, while for the efficient elimination of more complex PAH structures, the photocatalytic method is more recommended. Photocatalytic degradation has primarily relied on TiO2-based materials. However, this review focuses on the utilization of various metal oxide nanomaterials for the degradation or total removal of naphtalene from the environment, especially from wastewater. Precisely speaking, the photocatalytic activity of various nanomaterials is discussed, with an emphasis on photocatalytic degradation mechanisms and the identification of degradation intermediates. Key findings reveal that these materials hold substantial promise, and that photogenerated holes, superoxide radicals, and hydroxyl radicals play crucial roles in the degradation processes highlighting additionally the unique mechanisms of these processes. Important information about the intermediates and pathways of naphtalene degradation discussed in the mechanisms of degradation has been confirmed using gas chromatography-mass spectrometry (GC-MS).